Analysis of illicit drugs in municipal wastewater using LCMS/MS: A method validation study - Mohammad Azimuddin, Izani; Nurul `Azyyati, Sabri; Nurul Nadiah, Hamidon; Kooi, Yeong Khaw; Iekhsan, Othman; Mueller, Jochen; Tay, Joo Hui (Universiti Kebangsaan Malaysia, 2023)
An analytical method based on solid-phase extraction (SPE) liquid chromatography-tandem mass spectrometry (LC-MS/MS) for the determination of five illicit drugs, namely amphetamine (AM), methamphetamine (MA), 3,4- methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyamphetamine (MDA), and morphine (MOR) in municipal wastewater has been optimized and validated. Sample preparation was performed using Oasis MCX SPE cartridges. LC separation was performed using a Zorbax Eclipse Plus C18 RRHD column. The linearity of the calibration curve was between 5 ng/mL and 250 ng/mL, with determination coefficient (R2 ) greater than 0.99, except for morphine. The mean recoveries of target analytes ranged from 91.6 to 112%, and the method demonstrated good inter-day repeatability (coefficient of variation, CV ranged from 2 to 19%). The limit of detection (LOD) for AM, MA, MDMA, MDA, and MOR was 0.29, 0.37, 0.86, 1.09 and 7.56 ng/mL, respectively. The method was applied to municipal wastewater samples collected from sewage treatment plants in Kuantan, Pahang, in which AM, MA and MDA were detected in all 3 samples.